Perceived Effectiveness of Multicultural Education in Promoting Inclusivity - Hernandez, Aniano; Peñaflor, Ryan Jay; Cabral, Deiseree; Baladjay, Edelyn; Dela Luna, Lilian May; Relivo, Shiela; Canosam, Jamaica Maribeth; Bautista, Harren James; De Ramos, Lovelita; Hernandez, Lyra Crizelle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the perceived effectiveness of multicultural education in promoting inclusivity among elementary teachers of Lemery Pilot Elementary School. Specifically, it assessed the level of teachers’ implementation of multicultural education dimensions in terms of content integration, knowledge construction, prejudice reduction, equity pedagogy, and empowering school culture and social structure. It also examined teachers’ perceptions of inclusive education relative to system, support, cultural change, partnerships, and monitoring, and analyzed the relationship between these variables. A descriptive research design was employed using a researcher-made questionnaire administered through Google Forms to 57 elementary teachers selected through purposive sampling. Data were analyzed using weighted mean, Pearson’s r, and Cronbach’s Alpha through the Statistical Package for the Social Sciences (SPSS). The findings revealed that the dimensions of multicultural education were highly implemented across all areas, particularly in empowering school culture and social structure and content integration. Teachers also strongly agreed with all dimensions of inclusive education, including system, support, cultural change, partnerships, and monitoring. Furthermore, significant positive relationships were found between the implementation of multicultural education dimensions and teachers’ perceptions of inclusive education, indicating that stronger multicultural education practices are associated with more favorable perceptions of inclusivity. The study concluded that multicultural education is an effective approach in fostering inclusive learning environments and promoting respect, acceptance, and collaboration among diverse learners. It recommended strengthening multicultural education practices, providing continuous professional development opportunities for teachers, and encouraging greater collaboration among schools, families, and communities. This study aligns with Sustainable Development Goal (SDG) 4: Quality Education by promoting inclusive and equitable learning opportunities for all learners. The findings also support educational and social sustainability by strengthening inclusive school practices, fostering cultural understanding, and encouraging collaborative participation within the school community.